2022
DOI: 10.2460/javma.22.01.0043
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary professionals’ weight-related communication when discussing an overweight or obese pet with a client

Abstract: OBJECTIVE Pet weight may be difficult for veterinary professionals to address with clients, particularly when pets are overweight or obese. The objective of this study was to characterize the communication processes and content of weight-related conversations occurring between veterinary professionals and clients. SAMPLE Audio-video recordings of 917 veterinarian-client-patient interactions involving a random sample of 60 veterinarians and a convenience sample of clients. PROCEDURES Companion animal veteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Reduced odds of an obesity conversation for geriatric pets relative to younger animals were also seen in a recent observational study. 6 Placing less emphasis on weight reduction in older pets suggests that there are missed opportunities to improve quality of life in elderly pets, many of whom may also have arthritis or other conditions that could be improved through even moderate weight loss. 4,35 Given veterinary professionals' obligation to improve animal welfare, they are well positioned to help improve the quality of life of older overweight pets through weight loss.…”
Section: This Study Provides Preliminary Insights Into Veterinary Pro...mentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced odds of an obesity conversation for geriatric pets relative to younger animals were also seen in a recent observational study. 6 Placing less emphasis on weight reduction in older pets suggests that there are missed opportunities to improve quality of life in elderly pets, many of whom may also have arthritis or other conditions that could be improved through even moderate weight loss. 4,35 Given veterinary professionals' obligation to improve animal welfare, they are well positioned to help improve the quality of life of older overweight pets through weight loss.…”
Section: This Study Provides Preliminary Insights Into Veterinary Pro...mentioning
confidence: 99%
“…A recent observational study of 917 audio-video recorded appointments found that these topics, particularly calorie requirement calculations and discussions of physical activity, received limited attention during weight-related interactions. 6 Clear recommendations from the veterinary team for pet weight rechecks were also infrequent. 6 Participants in the present study may have responded based on a perception of an ideal interaction, as their responses align with some of the recommendations related to nutritional assessments in practice.…”
Section: This Study Provides Preliminary Insights Into Veterinary Pro...mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the wide‐ranging impact of obesity on animal health and welfare, it might be assumed that conversations about pet weight occur regularly in veterinary consultation rooms. Unfortunately, research suggests that these conversations often do not happen at the desired frequency 8,9 . Furthermore, of even greater concern, a recent survey reported that 82 per cent of dog owners and 78 per cent of cat owners identified their pet as being at an ideal weight, 10 which is at odds with studies assessing the prevalence of pet obesity 1–4 .…”
mentioning
confidence: 99%
“…For example, the prevalence of veterinary conversations surrounding weight and specifically pet obesity has been studied. 14 Nutritional assessment was reportedly more likely if patients had an existing or suspected health complaint, dietary-related condition, or evidence of malnutrition. 12 Therefore, veterinarians often focus on therapeutic foods as part of their recommendations for medical management of various diseases, but discussion of diet during appointments of healthy pets appears to be limited.…”
mentioning
confidence: 99%